Quantifying quality of WEB sites based on content - Venkata Raghavarao, Y; Sasidhar, K; Sastry, JKR; Chandra Prakash, V (International Journal of Engineering and Technology, 2018)
Information dissemination is taking place extensively through WEB and use of internet.  The quality and reliability of the information hosted on the WEB is questionable.  Many factors are to be considered for assessing the quality of the WEB sites. The Information hosted on the WEB would become valuable only when top quality of the same is maintained. Each quality factor can have many dimensions. There should be a mechanism of computing the quality of a web site quantitatively so that quality of a web site can be realistically measured.  Any subjective or objective way of measuring quality is questionable and can be prejudiced at times. Every factor as such must be measured the entire quality of a web site must be measured considering all the factors. One can develop a norm for quality of a factor and any deviation from the norm needs to be rectified and controlled.Among other factors quality of the content hosted on the WEB plays vital role. In this paper the computational method which can be used for computing the quality of a web site is presented considering all the dimensions of   content related quality factor.